2011
DOI: 10.1002/bem.20657
|View full text |Cite
|
Sign up to set email alerts
|

Effects of static magnetic fields on nicotinic cholinergic receptor function

Abstract: Ligand-gated ion channel kinetics were studied in mammalian transfected cells encoding adult mouse muscle acetylcholine (ACh) receptors. We measured macroscopic and single-channel currents using the outside-out and cell-attached patch-clamp configurations. Cultured cells were exposed to moderate intensity inhomogeneous static magnetic fields up to 180 mT and measurements were performed for temperatures ranging from 5 to 50 °C. We found no significant changes in ACh-elicited macroscopic or single-channel curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…The significance is greater due to the use of different electrical devices in everyday life and modern medicine. Moderateintensity magnetic fields (1 mT -1 T) can influence the activity of some ion channels in cell membranes but the mechanisms of actions still remain unknown (Tolosa et al 2011). Low frequency magnetic fields appear to increase charge movements within membrane protein, while electric fields during normal condition inhibited Na + /K + pump activity (Blank 1995(Blank , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…The significance is greater due to the use of different electrical devices in everyday life and modern medicine. Moderateintensity magnetic fields (1 mT -1 T) can influence the activity of some ion channels in cell membranes but the mechanisms of actions still remain unknown (Tolosa et al 2011). Low frequency magnetic fields appear to increase charge movements within membrane protein, while electric fields during normal condition inhibited Na + /K + pump activity (Blank 1995(Blank , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Wang, et al [93] results showed that 1.00 T and 1.13 T SMFs could increase cellular adenosine triphosphate (ATP). The biological effects of other SMFs(except for GMF and a HMF) were shown in Novitskii, et al [17]; Sullivan, et al [18]; Tolosa, et al [19]; Martino [20].…”
Section: The Hyperfine Coupling Mechanism Of Biological Effects On Otmentioning
confidence: 91%
“…Because of their ranges of intensity, they are the entire weak grade. The biological effects of other SMFs (except for GMF and a HMF)are reported [17][18][19][20]. More recent concerns have arisen about the potential effects of all different weak magnetic fields with the development of electric device era and information era [1].…”
Section: Introductionmentioning
confidence: 99%